Peningkatan Kualitas Air Sumur Gali Berdasarkan Parameter Besi (Fe) dengan Pemanfaatan Kulit Pisang Kepok - Jumiati Jumiati; Andi Susilawaty; Muh. Rusmin (HIGIENE: Jurnal Kesehatan Lingkungan, 2015)
Peel Kepok Banana (Musa acuminate L.) is one of the types of plants that can be used as an iron-lowering substances that exist in the water, lowering the levels of other heavy metals such as lead,manganese and other variables. Banana peel is made up of a number of nitrogen, sulfur and organiccomponents such as carboxylic acids, cellulose, hemicellulose, pectin substances and chlorophyll pigments containing galacturonic acid, arabinose, galactose and rhamnosa. Galacturonic acid can strongly bind metal ions which are sugar carboxyl functional groups. Based on preliminary examination inthe laboratory was dug well water levels as much substance Iron 1.67 mg / L, whereas the permissiblestandards for clean water in the Quality Standards Water Quality Standards according Permenkes No.416 / Menkes / PER / IX / 1990 was 1.0 mg / L. This research was conducted in Dusun Alekanrung Desa Kanrung Kecamatan Sinjai Tengah Kabupaten Sinjai and laboratory examinations were conductedin the Regional Environmental Agency of South Sulawesi (Laboratorium Badan Lingkungan Hidup Daerah Provinsi Sulawesi Selatan), which aims to determine how large a decrease in the level of the metalcontent of iron (Fe) by using banana peel kepok the dug well water . Type of research is a real experiment (Experiment True). The study design used was a pre-test-post-test with control group design, inwhich there is given a pretest before the treatment. Based on the results of research on Improvingthe Quality of Water Well Drilling Parameters Based on Iron (Fe) with Utilization of Banana peelKepok, it can be concluded that the laboratory used to test grade level of iron (Fe) in the dig well water is treated prior to 1.67 mg / L . Then the rate of decline in the levels of substances Iron (Fe) waterafter treated with Banana peel Kepok ie weighing 20 g were 0.80 mg / L or 52%, 40 g total of 0.94mg / L or 43.7% and 60 as much as 0.81 g or 51%. It is expected the people to pay attention to cleanwater that they use to perform first processing, one alternative is to use a banana peel kepok. To other researchers, it is advisable to examine the benefits of this kepok banana peel with indicators ofother parametersKeyword: peel kepok banana, dig well water, iron